Protecting trade secret from theft and corporate espionage: business entity v employee & competitors - Abd. Jalil, Juriah; Hassan, Halyani (2018)
Trade secret is a gold nugget that determines the success and survival of a business entity. It provides a business entity with a competitive value over its rival. However protecting a trade secret is not an easy task especially from current and former employee as well as from competitors. The task is made difficult with the availability of technological devises that can be used to steal the information from inside and outside of the business organization. This paper highlights the importance of protecting trade secrets from theft of trade secret and corporate espionage by business entity and to recommend the best practice on how to protect from legal, administrative and technical perspectives. This study is significant to educate business entity especially SME on the importance of protecting trade secrets in this digital age and for the government to strengthen the law on protecting trade secrets. In this regards, protecting trade secrets is equivalent to protecting the economy of the country.